Kolozsvár-Szeged : egy egyetemtörténeti vita törésvonalai - Keczer, Gabriella; Pintér, Lajos (Közép-Európai Közlemények, 2011)
How old is the University of Szeged? This question has been frequently asked inside and outside the institution since the change of the political system in Hungary. Until which date can the history of the university be traced back? Is it the time when an institution was established in Kolozsvár by Báthory in 1581? Or is it the year of 1872, when the Ferenc József University was opened in Kolozsvár? Or is it 1921, when higher education has begun in Szeged? The University of Szeged launched a debate on this issue in 2007. The debate was going on in different meetings and in the newspaper of the university. At least the Senate of the university has accepted the following: the University of Szeged is the spiritual-cultural heir of the Báthory-institution established in 1581, thus this date is the founding of the University of Szeged. In our paper we analyze the most important aspects of the debate, using the archives of the university newspaper.